Game play therapy : therapeutic use of games with children and adolescents - Stone, Jessica (Child psychologist); Schaefer, Charles E. (Hoboken : John Wiley & Sons Inc., 2020)
'The purpose of this comprehensive,'state-of-the art' guidebook is to provide mental health practitioners with essential information about the field of Game Play Therapy, including its theoretical foundations, and practical applications to children and adolescents. It will describe both classic games that have stood the test of time as well as the latest innovations and advances in game play approaches, such as Electronic Games and Disorder-Specific Games. Not withstanding the wide spread and growing practice of Game Play Therapy across the globe, most child and adolescent practitioners have received little or no formal training about why and how to use this intervention most effectively. Thus, the chapter contributors in the volume will provide expert advice on how to select the most useful therapy games (over 700 that are now available), the'nuts-and-bolts' of administering and using these game effectively, case illustrations of the process of game therapy, and empirical evidence of its effectiveness. The contributors will all be credentialed play therapists with extensive experience practicing Game Play Therapy'--
Revision of: Game play / edited by Charles Schaefer and Steven E. Reid. 2001. 2nd.
Includes bibliographical references and index.
Keywords: Play therapy; Child psychotherapy; Games -- Therapeutic use